2012
DOI: 10.1016/j.jvs.2011.07.084
|View full text |Cite
|
Sign up to set email alerts
|

Remote and local ischemic preconditioning equivalently protects rat skeletal muscle mitochondrial function during experimental aortic cross-clamping

Abstract: Acute and chronic ischemia induce mitochondrial dysfunction in human skeletal muscles, and improving muscle mitochondrial function improves subjects’ status. Compared with local ischemic preconditioning (IPC), remote IPC (rIPC) appears easier to perform and is safer for the vessel and territory involved in ischemic injury. This study demonstrates that the muscle protection afforded by rIPC is equivalent to that achieved by IPC. Acknowledging that IPC procedures should be specifically adapted to patient charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…8 Recently, it was also demonstrated that both the direct and remote approach to ischemic preconditioning provide mitochondrial protection of skeletal muscle in rats undergoing ACC. 7 Disruption of mitochondrial function increases the risk of disturbing homeostasis of electrolytes and energy balance, which in turn increases risk of cardiac arrhythmia. 23 Although most respiratory parameters remained unaltered after surgery within RIPC, we did observe elevated ↑RR Cr and V creatine , along with lower app K m (ADP+Cr) pre ACC compared with post ACC, which indicates greater ADP sensitivity in the presence of creatine early in surgery compared with later in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recently, it was also demonstrated that both the direct and remote approach to ischemic preconditioning provide mitochondrial protection of skeletal muscle in rats undergoing ACC. 7 Disruption of mitochondrial function increases the risk of disturbing homeostasis of electrolytes and energy balance, which in turn increases risk of cardiac arrhythmia. 23 Although most respiratory parameters remained unaltered after surgery within RIPC, we did observe elevated ↑RR Cr and V creatine , along with lower app K m (ADP+Cr) pre ACC compared with post ACC, which indicates greater ADP sensitivity in the presence of creatine early in surgery compared with later in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A progressive defect in respiratory Complex I has been detected in human myocardium from patients at early stages of heart failure [25]. Studies of mitochondrial respiration in rodent skeletal muscle have implicated both a specific ischemia-induced dysfunction and subsequent protection by ischemic preconditioning localized to Complexes I and II in the aftermath of acute ischemia [6], whereas others observed a general malfunction of all respiratory complexes after ischemia-reperfusion [26]. The inconsistency in the precise localization of the respiratory alterations might be due to differences in species, tissue or severity of the ischemic challenge, which complicates a direct comparison with our results.…”
Section: Discussionmentioning
confidence: 99%
“…With reoxygenation, the respiratory chain of undamaged mitochondria produces ATP and the mitochondrial membrane potential is recovered. However, in cells subjected to ischemia, reperfusion further alters the activity of mitochondrial complexes I-IV as described in experimental models and PAD (28,108,146,147,176,179). The impaired function decreases ATP synthesis (Fig.…”
Section: ϩmentioning
confidence: 90%
“…Ischemic preconditioning is frequently used in acute experimental models and appears to be protective (88,135,176). Importantly, the report of Mansour et al (108) that remote and local ischemic preconditioning equivalently protect skeletal muscle mitochondrial function during lower limb I/R opens therapeutic avenues, since remote (at a distant organ, not suffering from ischemia) ischemic preconditioning is easier to accomplish than local preconditioning. In the context of chronic PAD, ischemic conditioning, a natural phenomenon that occurs during walking, must be considered a part of PAD physiopathology.…”
mentioning
confidence: 99%